The Mediator Complex Subunits MED14, MED15, and MED16 Are Involved in Defense Signaling Crosstalk in Arabidopsis - Wang, Chenggang; Du, Xuezhu; Mou, Zhonglin (Frontiers in Plant Science, 2016)
Mediator is a highly conserved protein complex that functions as a transcriptional coactivator in RNA polymerase II (RNAPII)-mediated transcription. The Arabidopsis Mediator complex has recently been implicated in plant immune responses. Here, we compared salicylic acid (SA)-, methyl jasmonate (MeJA)-, and the ethylene (ET) precursor 1-aminocyclopropane-1-carboxylic acid (ACC)-induced defense and/or wound-responsive gene expression in 14 Arabidopsis Mediator subunit mutants. Our results show that MED14, MED15, and MED16 are required for SA-activated expression of the defense marker gene PATHOEGNESIS-RELATED GENE1, MED25 is required for MeJA-induced expression of the wound-responsive marker gene VEGATATIVE STORAGE PROTEIN1 (VSP1), MED8, MED14, MED15, MED16, MED18, MED20a, MED25, MED31, and MED33A/B (MED33a and MED33B) are required for MeJA-induced expression of the defense maker gene PLANT DEFENSIN1.2 (PDF1.2), and MED8, MED14, MED15, MED16, MED25, and MED33A/B are also required for ACC-triggered expression of PDF1.2. Furthermore, we investigated the involvement of MED14, MED15, and MED16 in plant defense signaling crosstalk and found that MED14, MED15, and MED16 are required for SA- and ET-mediated suppression of MeJA-induced VSP1 expression. This result suggests that MED14, MED15, and MED16 not only relay defense signaling from the SA and JA/ET defense pathways to the RNAPII transcription machinery, but also fine-tune defense signaling crosstalk. Finally, we show that MED33A/B contributes to the necrotrophic fungal pathogen Botrytis cinerea-induced expression of the defense genes PDF1.2, HEVEIN-LIKE, and BASIC CHITINASE and is required for full-scale basal resistance to B. cinerea, demonstrating a positive role for MED33 in plant immunity against necrotrophic fungal pathogens.